2002
DOI: 10.1103/physrevb.66.174514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epitaxial strain on the growth mechanism inYBa2Cu3O

Abstract: We report on the growth mechanism of YBa 2 Cu 3 O 7Ϫx . Our study is based on an analysis of ultrathin YBa 2 Cu 3 O 7Ϫx ͑YBCO͒ layers in c-axis-oriented YBa 2 Cu 3 O 7Ϫx /PrBa 2 Cu 3 O 7 superlattices. We have found that the release of epitaxial strain in very thin YBCO layers triggers a change in the dimensionality of the growth mode. Ultrathin epitaxially strained YBCO layers with thickness below 3 unit cells grow in a blockby-block two-dimensional mode that is coherent over large lateral distances. Meanwhil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…The observation of a reduced c-axis for ultrathin films is in good agreement with results for sputter deposition [36,37], but contradict earlier results by pulsed laser deposition [20]. An important point is the SrRuO 3 cap layer in these experiments, which was not present in the other PLD experiments.…”
supporting
confidence: 76%
“…The observation of a reduced c-axis for ultrathin films is in good agreement with results for sputter deposition [36,37], but contradict earlier results by pulsed laser deposition [20]. An important point is the SrRuO 3 cap layer in these experiments, which was not present in the other PLD experiments.…”
supporting
confidence: 76%
“…We have used the PBCO buffer since aside from providing a better growth as discussed above, it has been reported that YBCO single films directly grown on STO substrates have smaller T c values as compared with samples grown in PBCO buffers. 34 Both samples show the critical temperature to decrease when the thickness of the superconducting layer is reduced. However, while YBCO/LCMO/STO bilayers show broad tails for the smallest YBCO thicknesses pointing to a 35,36 as a result of epitaxial strain relaxation or dimensionality effects, but the decrease is more pronounced for samples with ferromagnetic layers as a result of the strong F/S interplay observed previously in trilayers and superlattices.…”
Section: Resultsmentioning
confidence: 99%
“…This can be understood considering that YBCO layers in the superlattice are fully decoupled, and thus the observed behavior is in fact the same that could be expected for a single YBCO layer of identical thickness and perfect surfaces. Unfortunately in practice YBCO single films five unit cells thick exhibit depressed T c values ͑60 K͒ compared to superlattices ͑80 K͒, resulting from surface imperfections and exposure to ambient conditions, 30 and thus comparison of the dissipation properties is meaningless. BL barrier effects are not observed in the coupled superlattice since the relevant length scale to compare with a 0 is sample thickness ͑200 nm͒.…”
Section: Fig 4 Superconducting Transitions Of Sample Ybcomentioning
confidence: 99%